Heritage revitalisation strategy: the saviour of Petaling Street / Zalina Samadi ... [et al.] - Samadi, Zalina; Bakri, Aidatul Fadzlin; Ramli, Saidatul Haziah; Shaari, Mariam Felani; Haider, Laila (UiTM Press, 2024)
In revitalising heritage cities, Ross (2024) criticised the dominancy of urban preservation and management in cities that focus more on tangible than intangible heritage. The urban law highlighted that ‘image and identity’ are essential to represent a morphology and tangible and intangible heritage of specific urban avenues. Xiang & Mohamad (2023) unveiled that the front and back of heritage shophouses at Petaling Streets are adaptive usage. Heritage Revitalisation Stragey (HRS) is not new to Canadian, European, Middle Eastern, Chinese and Russian cities, which the tangible and intangible heritage treasures are valued equally in a strategic approach. This study evaluates the existing Heritage Revitalisation Strategy (RS) dedicated for the local authority of Dewan Bandaraya Kuala Lumpur (DBKL) and the Think City in valorising the heritage street of Petaling. Even though various methods were implemented in most heritage streets in Kuala Lumpur which were not successful, therefore a remarkable approach of HRS shall be tested to Petaling Street to groom the public place’s ambience. This research aims to identify the best approach applicable to urban heritage streets globally that is applicable urban heritage streets in Kuala Lumpur. Researchers conducted semi-structured interviews with the heritage manager of Kuala Lumpur City Hall and Think City’s personnel, visual observations, digital photo analysis, and Focus Group Discussion (FGD) with shop owners were applied to establish a balanced strategy between the existing HRS and the Petaling Street’s version. Valorising the intangible and tangible built heritage as daily practices of the local street community as part of the street culture. Still, a proper Heritage Revitalisation Strategy (HRS) is urgently required specifically for our urban heritage street. Understanding this rare strategy for transforming into the street is critical in valorising its value. A proper RS by the DBKL management to further elevate its function as a tourist boosting factor is a catalyst for other avenues.